An experimental study of the effect of anxiety on lexical processing of college students: evidence from true-false word judgment and semantic category judgment tasks - Huiyong, Zhang; Xinping, Pu (Frontiers in Psychology, 2025)
IntroductionThis study examined the effect of anxiety on lexical processing among college students with anxiety in China.MethodsWe conducted two experiments in a stressful environment to induce anxiety. Experiment 1 investigated the effect of anxiety on lexical processing through a true-false word judgment task, while Experiment 2 further explored this effect using a semantic category judgment task.ResultsBoth experiments revealed no significant difference in the accuracy of lexical judgments between participants with high and low anxiety. However, there was a notable difference in the reaction times for lexical judgments, with high-anxiety participants exhibiting longer reaction time compared to their low-anxiety counterparts. This indicates a decrease in the efficiency of lexical processing among those with high anxiety.ConclusionThis study confirms that anxiety diminishes lexical processing efficiency without affecting lexical judgment performance. These findings support the processing efficiency theory.